The use of pharmacogenetics in clinical practice for the treatment of individuals with HIV infection in Thailand - Bushyakanist A; Puangpetch A; Sukasem C; Kiertiburanakul S (Dove Medical Press, 2015)
Asalaysa Bushyakanist,1 Apichaya Puangpetch,2,3 Chonlaphat Sukasem,2,3 Sasisopin Kiertiburanakul11Department of Medicine, 2Division of Pharmacogenomics and Personalized Medicine, Department of Pathology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 3Laboratory for Pharmacogenomics, Somdech Phra Debaratana Medical Center (SDMC), Ramathibodi Hospital, Bangkok, ThailandObjectives: The objectives of this study were to describe the use of pharmacogenetics in clinical practice for the treatment of individuals with human immunodeficiency virus (HIV) infection and to determine the treatment outcomes of HIV-infected patients in whom pharmacogenetic testing was performed.Methods: This study involves a retrospective collection of medical records of HIV-infected patients who attended Ramathibodi Hospital during January 2011 to November 2014 and in whom pharmacogenetic testing was performed. We reviewed patients' characteristics, reasons for pharmacogenomic testing, results of human leukocyte antigen-B* (HLA-B*) 5701, HLA-B*3505, HLA-B*4001, CYP2B6, and antiretroviral drug (ARV) levels, treatment planning after the physicians were informed the results, and outcome after changing the treatment.Results: A total of 103 HIV-infected patients with a median age of 46 (range, 20–85) years were enrolled, and 68.9% of them were male. The reasons for pharmacogenomic testing were having adverse drug reactions besides rash (37.9%), screening before prescribing ARV (36.9%), choice of next ARV (19.4%), and confirmation of the cause of skin rash (5.8%). After the physicians knew the results, they adjusted the treatment plan including changing the regimens, changing the ARV dose for avoiding toxicity, and stopping ARV. Among 45 patients, side effects, such as dizziness from efavirenz or rash from abacavir, were improved in 96.4%. Among 27 patients, abnormal laboratory results, such as renal insufficiency from tenofovir or anemia from zidovudine, were improved and some returned to normal in 59.3%. HIV RNA was undetectable after treatment adjustment in 94.9%.Conclusion: The benefits of pharmacogenetic testing are either guiding the initial drug regimen or individualizing regimen, increasing efficacy, and simultaneously avoiding adverse drug reactions. Use of pharmacogenetic testing in HIV-infected Thai adults should be considered.Keywords: adverse drug reaction, antiretroviral drugs, clinical practice, HIV, pharmacogenetics, Thailand